EFFECTIVENESS OF ECONOMIC POLICIES IN COMBATING INFLATION IN NIGERIA - Afolabi, Sola; Ayodele, Thomas; Akinyede, Oyinlola; Ojedele, Mofoluwaso; Adeyanju, Olanrewaju (European Journal of Applied Sciences, 2021)
This study assessed the effectiveness of economic policies (monetary and fiscal policies) in fighting Nigeria's Inflation. Secondary data obtained over thirty-eight years (1981-2018) from the Central Bank of Nigeria (CBN)'s statistical bulletins were used. The econometric test was carried out on the data, which included the ADF-Fisher unit root test and the Johansen co-integration test. A Vector Autoregressive model was used to specify the relationship between the independent variables (Interest rate, Money supply and Liquidity ratio) and the dependent variable (Inflation rate), through the least squares technique. The result revealed that money supply and lending rate have direct and significant influence on inflation (p-values<0.05). However, external debt and government expenditure do not significantly influence inflation. The study concluded that monetary policy is more effective than fiscal policy in combating inflation. Therefore, it was recommended that financial institutions in Nigeria should comply with specified prudential guidelines on monetary policy implementations. Furthermore, the Central Bank of Nigeria should be allowed to carry out her functions without pressure or hinderance from any arm of government.